Struggle for the heartland : the campaigns from Fort Henry to Corinth - Engle, Stephen Douglas (Great campaigns of the Civil War., 2001)
Struggle for the Heartland tells the story surrounding the military campaign that began in early 1862 with the advance to Fort Henry and culminated in late May with the capture of Corinth, Mississippi. The first significant Northern penetration into the Confederate west, this campaign saw the military coming-of-age of Ulysses S. Grant and offered a hint as to where the Federals might win the war. For the South, it dashed any hopes of avoiding a protracted conflict. Stephen D. Engle colors in the details that bring great clarity and new life to the scene of these battles as well as to the social and political context in which they occurred.